2020
DOI: 10.1038/s41537-020-00125-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying signals associated with psychiatric illness utilizing language and images posted to Facebook

Abstract: Prior research has identified associations between social media activity and psychiatric diagnoses; however, diagnoses are rarely clinically confirmed. Toward the goal of applying novel approaches to improve outcomes, research using real patient data is necessary. We collected 3,404,959 Facebook messages and 142,390 images across 223 participants (mean age = 23.7; 41.7% male) with schizophrenia spectrum disorders (SSD), mood disorders (MD), and healthy volunteers (HV). We analyzed features uploaded up to 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 69 publications
2
27
2
1
Order By: Relevance
“…When considering the width, height, and aspect ratio (the ratio of width to height), we did not find any differences between the two groups. This is contrary to findings by Birnbaum et al (24) who analyzed images posted to Facebook and found that participants with SSD and MD posted images that were smaller in width and height than HV posts. Of note, different social media platforms offer unique image manipulation options and affordances, which could be one explanation for differing results.…”
Section: Characteristics Of Image Posts On Instagramcontrasting
confidence: 99%
See 4 more Smart Citations
“…When considering the width, height, and aspect ratio (the ratio of width to height), we did not find any differences between the two groups. This is contrary to findings by Birnbaum et al (24) who analyzed images posted to Facebook and found that participants with SSD and MD posted images that were smaller in width and height than HV posts. Of note, different social media platforms offer unique image manipulation options and affordances, which could be one explanation for differing results.…”
Section: Characteristics Of Image Posts On Instagramcontrasting
confidence: 99%
“…We included the entire archive for analysis including pre and post diagnosis data as psychotic symptoms are known to emerge well in advance of receiving the diagnosis (41). Further, prior work has demonstrated that digital media traces on Facebook showed changes over a year before the initial diagnosis (24). We selected a minimum criteria of at least 5 posts over a timespan of at least 3 months-a timespan previously used as a time window for classification tasks (24).…”
Section: Data Extraction Exclusion and Subject Matchingmentioning
confidence: 99%
See 3 more Smart Citations